What is good for General Motors? : solving America's industrial conundrum - Crumm, Thomas A. (Algora Pub., 2010)
An insider exposes the strategic decisions that have caused the foundation of America?s industrial sector to crumble, then lays out a plan for its restoration. The author led GM Chairman John Smale?s Scenario Planning Staff in the mid-1990s and Roger Smith?s development of a Saturn expansion proposal in the late-1980s after a career in GM plant operations designing and managing manufacturing systems.